The imaging dynamic changes in the malignant transformation of an epidermoid cyst: a case report and literature review - Yang, Tian; Hu, Jibo; Li, Lele; Xu, Houyun; Zhang, Caijuan; Huang, Zhilan; Yang, Jun; Zhang, Huiqing (Frontiers in Neurology, 2024)
Malignant transformation of epidermoid cysts is a rare complication. Most of the previously reported cases have involved postoperative malignant transformations. We present a case of malignant transformation of a nonpostoperative epidermoid tumor into squamous cell carcinoma (SCC) that occurred in a 61-year-old Chinese woman. The patient’s initial cranial MRI scan showed an epidermoid cyst with marginal enhancement in the pre-pontine cistern, and the lesion gradually enlarged after 10 months. A craniotomy was performed using to remove part of the tumor via the right retrosigmoid approach, and postoperative pathology confirmed that the transformation of the epidermoid cyst was malignant. Our case study suggests that the possibility of malignant transformation of epidermoid cyst should not be ignored on the basis of enhanced imaging features, regardless of whether they are nodular, annular, or patchy, as is the case for inflammation. Strict follow-up is required for early detection of malignant transformation to prompt correspondingly early clinical treatment.